The impact of an autism spectrum disorder diagnosis on family life (Research, Society and Development, 2022)
Introduction: The autistic spectrum disorder is a neurodevelopmental disorder characterized by behavioral changes, social interaction and communication deficit. These manifestations cause changes in family life. General objective: To analyze the impact of the diagnosis of autistic spectrum disorder on family life. Method: This is an integrative review research. The search sources were SciELO, MEDLINE, Lilacs and Centers for Disease Control and Prevention (CDC). Results and Discussion: The study showed that there is a deficit of knowledge of family members about the treatment of autism spectrum disorder, as well as difficulties in accepting the diagnosis and dealing with the situation. Among the main impacts the study showed: stress, family disruption, difficulties in treatment and lack of support network from health institutions and monitoring of health professionals. Conclusion: Caring for children with autism spectrum disorder is a great challenge and a physical and psychological burden on family members. However, when the disorder is diagnosed and treated early, it improves child development, family bonding and social interaction, minimizing the suffering of all family members.